BUSINESS INTELLIGENCE AND ORGANISATIONAL PERFORMANCE IN MANUFACTURING ORGANISATIONS OF LAGOS METROPOLIS - Onikoyi, Idris Adegboyega; Adebayo, Adeyeye Victor; Omotola, Ojodu Hameed; Odeh, Callistus Destiny (Farabi Journal of Social Sciences, 2025)
Purpose. The purpose of this study is to examine the influence of business intelligence on organizational performance within manufacturing organizations. Specifically, it explores the role of environmental intelligence, consumer intelligence, and business intelligence as drivers of competitive advantage and market share growth. Design/methodology/approach. A quantitative research design was adopted, using a structured questionnaire as the primary data collection tool. Data were obtained from 150 respondents working in manufacturing organizations. Statistical analysis was conducted to identify correlations between business intelligence dimensions and measures of organizational performance. Findings. The results reveal that environmental intelligence has a positive correlation with organizational performance, while consumer intelligence significantly influences market share. Moreover, the study finds that business intelligence functions as a key source of competitive advantage in manufacturing firms. Originality. This research contributes to the growing body of knowledge on strategic information systems by highlighting how business intelligence tools enhance competitiveness and sustainability. The study recommends that organizations develop clear business intelligence objectives aligned with corporate goals to ensure long-term performance improvement. Keywords: Business intelligence; Organizational performance; Business environment, customer intelligence.